Living downtown : the history of residential hotels in the United States - Groth, Paul Erling (Berkeley : University of California Press, 1994)
From the palace hotels of the elite to cheap lodging houses, residential hotels have been an element of American urban life for nearly two hundred years. Since 1870, however, they have been the target of an official war led by people whose concept of home does not include the hotel. Do these residences constitute an essential housing resource, or are they, as charged, a public nuisance? Living Downtown, the first comprehensive social and cultural history of li.
Conflicting Ideas about Hotel Life -- Palace Hotels and Social Opulence -- Midpriced Mansions for Middle Incomes -- Rooming Houses and the Margins of Respectability -- Outsiders and Cheap Lodging Houses -- Building a Civilization without Homes -- Hotel Homes as a Public Nuisance -- From Scattered Opinion to Centralized Policy -- Prohibition versus Pluralism.
Includes bibliographical references (pages 371-386) and index.
Print version record.
English.
JSTOR
Keywords: Single-room occupancy hotels -- United States -- History; Architecture and society -- United States; City and town life -- United States; Housing -- United States -- Sociological aspects; Single people -- Housing -- History; City and town life -- United States; Maisons de chambres -- États-Unis -- Histoire; Architecture et société -- États-Unis.; Vie urbaine -- États-Unis.; Personnes seules -- Logement -- Histoire; BUSINESS & ECONOMICS -- Small Business; SOCIAL SCIENCE / Sociology / Urban; Architecture and society; City and town life; Housing -- Sociological aspects; Single people -- Housing; Single-room occupancy hotels; United States; Aparthotel; Geschichte; USA; Hotels; Pensions; Sociologia urbana; Habitacao; Arquitetura moderna (estados unidos); Hoteis (arquitetura); Hotels; United States; History